1997
DOI: 10.1159/000026469
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cortisol Profiles in Chronic Fatigue Syndrome

Abstract: Salivary cortisol profiles (hourly sampling over a 16-hour period) of 10 patients with chronic fatigue syndrome (CFS) but without concurrent depressive disorder were compared with those of 10 healthy volunteers matched for age, sex and menstrual cycle. The mean saliva cortisol concentration over the 16-hour period was slightly but significantly greater in the patients than the controls (p < 0.05). These findings are at variance with earlier reports that CFS is a hypocortisolaemic state and suggest that in CFS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…This has not been previously described in CFS -as two small studies did not find such differences [15,16] although it has been reported in fibromyalgia [18], pain syndromes [19] and of course depressive illness [20]. However, in each of these reports the lack of diurnal variation has accompanied elevated plasma cortisol levels rather than the mild hypo-cortisolaemia generally found in CFS.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This has not been previously described in CFS -as two small studies did not find such differences [15,16] although it has been reported in fibromyalgia [18], pain syndromes [19] and of course depressive illness [20]. However, in each of these reports the lack of diurnal variation has accompanied elevated plasma cortisol levels rather than the mild hypo-cortisolaemia generally found in CFS.…”
Section: Discussionmentioning
confidence: 70%
“…The effect sizes of these differences, extracted from the published figures, are -0.7, -3.8 and +5.5 respectively. Another group have also found a non-significant reduction in baseline morning cortisol levels [14], while two other small studies have recently reported non-significant elevations in morning cortisol [15,16], but none of these have reported exact figures that would allow effect size computation. Demitrack et al [2] reported significantly lower evening cortisol levels in CFS (effect size -2.9), which still requires replication as the trend of our result (effect size +0.2) and those of other published reports [15,16] is against this.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, in about half of the investigations there was evidence for lowered cortisol levels in CFS. There is only 1 report of elevated salivary cortisol levels in CFS [16] . In all the other studies, no differences were found between CFS patients and control individuals.…”
Section: Hpa Axis Disturbances In Cfsmentioning
confidence: 99%
“…Because abnormal thyroid function can be a common cause of fatigue, and this fatigue resolves with adequate treatment [7], patients with hypo-or hyperthyroidism are excluded from a diagnosis of CFS. Several studies have suggested that mild hypocortisolemia might be a cause of the fatigue in CFS [8][9][10], but other studies have failed to find abnormal cortisol (CORT) levels in CFS patients [11] or have found elevated adrenocortical hormones [12]. Because the subjects in this study were female, and ovarian cycles and estrogens can affect pituitary-adrenal function, plasma estradiol (E 2 ) was measured in this study.…”
mentioning
confidence: 93%